Study Of Islamic Character Values In Ireng Mask Dance For Elementary School At Mis Al-Islam Tempel - Alfian Eko Widodo Adi Prasetyo; Rizky Eka Mahardika; Ikha Sulis Setyaningrum (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study aims to describe the value of character education values in implementing extracurricular Ireng mask dance at MIS Al Islam Tempel. This research approach uses qualitative description. Data collection techniques using observation, interviews, and documentation. The results showed that The character implementation process is carried out through several stages, namely first, providing knowledge and understanding (moral knowing) about the art of Ireng mask dance and the raised character values. Second, extracurricular participants are supported and conditioned to familiarize themselves with character values (moral feeling) through student activeness in activities. Finally, with full awareness, students will get used to implementing character values (moral action) in their social environment. The character education values developed are religion, hard work, self-confidence, discipline, love for the country, social care, responsibility, and environmental care.